Distance learning for Indonesian Mathematics Students with Hearing Impairments in Pandemic Situation: A Case Study - Fadhilah Rahmawati; Megita Dwi Pamungkas; Aprilia Nurul Chasanah; Arief Budi Wicaksono; Yesi Franita; Zuida Ratih Hendrastuti (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to identify the distance learning process of deaf students during the pandemic. This research is qualitative research with a case study approach. The subjects of this study were mathematics teachers, deaf students, and stakeholders. The research was carried out at the SLBN Kota Magelang and SLB-B YPPALB Magelang . Data collection techniques in this study were carried out by questionnaires, interviews, and document studies. The main instrument in this study was the researcher, while the auxiliary instruments were questionnaires and interview guidelines. The validity used in this research is source triangulation. The results showed that the mathematics distance learning process for deaf students could be implemented in various ways and could be adapted to school conditions and student conditions. Distance learning can be done with the help of media in hand-out modules taken at school before the mathematics learning schedule is implemented. In addition, the distance learning process on the mathematics topic of deaf students can also be carried out through learning videos with additional translated texts. Deaf students can simultaneously watch videos and read explanations from math teachers.